Нормативно-правове забезпечення системи антикризового управління промисловим підприємством - Погорєлов, Микола Іванович; Сиром'ятников, Дмитро Євгенович; Сиром'ятникова, Оксана Валеріївна (НТУ "ХПІ", 2017)
Чинне законодавство України в сфері банкрутства являє собою складну систему правових норм і служить основою нормативно-правового забезпечення системи антикризового управління промисловим підприємством, основним завданням якого є виключення можливості банкрутства підприємства. Визначено завдання щодо подальшого реформування процедури банкрутства, що дозволить досягти збалансування інтересів боржника і кредиторів при максимальному задоволенні їх вимог в короткі терміни і дозволить запобігти фіктивного банкрутства.

The main task of the crisis management is to eliminate the possibility of bankruptcy of the enterprise. Insolvency (bankruptcy) is the inability of the debtor to fully satisfy the creditors' claims for monetary obligations recognized by the arbitration court and fulfill the obligation to pay mandatory payments. The economic inconsistency of one enterprise affects the financial position of other economic entities that are its counterparties. Bankruptcy allows business entities to improve their financial condition and achieve financial stability. The role of bankruptcy is to exclude insolvent enterprises from economic circulation. The current legislation of Ukraine in the field of bankruptcy is a complex system of legal norms and serves as the basis for the regulatory support of the crisis management system of an industrial enterprise whose main task is to exclude the possibility of bankruptcy of the enterprise. The tasks of further reforming the bankruptcy procedure are determined, which will allow to quickly balance the interests of the debtor and creditors with the maximum satisfaction of their requirements and help to prevent fictitious bankruptcies.
Keywords: антикризове управління; банкрутство; боржник; кредитор; ліквідація; платоспроможність; crisis management; bankruptcy; debtor; creditor; liquidation; solvency